Individualism, Collectivism, and Allocation Behavior: Evidence from the Ultimatum Game and Dictator Game - Jingjing Jiao; Jun Zhao (Behavioral Sciences, 2023)
Studies have demonstrated the influence of the cultural values of individualism and collectivism on individuals’ economic behavior (e.g., competition and trade). By using individualistic and collectivistic texts to prime participants’ minds in a lab experiment, we investigated the impact of the cultural values of individualism and collectivism on allocation behavior in an ultimatum game (UG) and dictator game (DG). In the dictator game, we found that participants in the collectivism-priming condition reported a slightly higher mean offer than in the individualism-priming condition, and participants had an average higher acceptance rate of the proposers’ offer in the collectivism-priming (vs. individualism-priming) condition in the ultimatum game. Our findings suggest that participants exhibit more altruistic allocation behavior and are more tolerant of unfair allocation behavior after being primed by the collectivistic (vs. individualistic) texts. In comparison with participants who did not undergo initiation, we also found that Chinese participants who had been influenced by collectivist values for a long time remained unaffected after the initiation of collectivism, but shifted their allocation behavior (i.e., showed decreased altruistic allocation behavior and reduced tolerance of unfair allocation behavior) when individualism was primed.